Device-to-device (D2D) reliable transmission in the internet of things - Tanweer Alam (Jurnal Informatika, 2021)
D2D stands for device-to-device communication, which is likely to perform a major impact in future mobile communications because it offers ultra-low latency for end user’s direct conversation. Throughout minimizing latency, increasing strength and improved transmission efficiency, and expanding telecommunication services, D2D services are seen as a successful innovation for emerging mobile communications. The D2D networking makes a unique contribution to the wireless world by simplifying data transfer among devices connected. D2D networking makes use of adjacent two nodes to maximize the use of existing infrastructure, low latency, boost throughput and expand service functionality. Within wireless networks, D2D communication is described as immediate interaction among two mobile devices without passing through the access point or network infrastructure. The fully integrated wireless communication would be built by integrating D2D and the Internet of Things. D2D enables the larger number of devices to be paired at a higher bandwidth frequency and with minimum latency. Building a new reliable framework for D2D communication of smart devices can be an important framework for improving the reliability of communication. Internet of Things is the process of communicating and sharing information between nearby devices. But there are many challenges to secure and reliable communication. Amongst the major concerns for wireless transmission has been identified as communication trust, and overcoming this issue could lead to sustained expansion in the usage and popularity of the Internet of Things. The proposed study develops a system for providing internet access to a network of smart devices connected to the internet of things. The significant contributions link the latest findings that incorporate the interaction framework's stability and provides secure internet networking for connected devices.